Simultaneous suppression of PKM2 and PHGDH elicits synergistic anti-cancer effect in NSCLC - Kaixuan Wang; Hao Lu; Xinmiao Wang; Qingxia Liu; Jinxia Hu; Yao Liu; Yao Liu; Meihua Jin; Dexin Kong (Frontiers Media S.A., 2023)
Metabolic reprogramming is a hallmark of human cancer. Cancer cells exhibit enhanced glycolysis, which allows glycolytic intermediates to be diverted into several other biosynthetic pathways, such as serine synthesis. Here, we explored the anti-cancer effects of the pyruvate kinase (PK) M2 inhibitor PKM2-IN-1 alone or in combination with the phosphoglycerate dehydrogenase (PHGDH) inhibitor NCT-503 in human NSCLC A549 cells in vitro and in vivo. PKM2-IN-1 inhibited proliferation and induced cell cycle arrest and apoptosis, with increased glycolytic intermediate 3-phosphoglycerate (3-PG) level and PHGDH expression. The combination of PKM2-IN-1 and NCT-503 further suppressed cancer cell proliferation and induced G2/M phase arrest, accompanied by the reduction of ATP, activation of AMPK and inhibition of its downstream mTOR and p70S6K, upregulation of p53 and p21, as well as downregulation of cyclin B1 and cdc2. In addition, combined treatment triggered ROS-dependent apoptosis by affecting the intrinsic Bcl-2/caspase-3/PARP pathway. Moreover, the combination suppressed glucose transporter type 1 (GLUT1) expression. In vivo, co-administration of PKM2-IN-1 and NCT-503 significantly inhibited A549 tumor growth. Taken together, PKM2-IN-1 in combination with NCT-503 exhibited remarkable anti-cancer effects through induction of G2/M cell cycle arrest and apoptosis, in which the metabolic stress induced ATP reduction and ROS augmented DNA damage might be involved. These results suggest that the combination of PKM2-IN-1 and NCT-503 might be a potential strategy for the therapy of lung cancer.